The Role of Islamic Criminal Law In Combating Criminal Acts of Corruption Against Government Grant Funds: A Case Study of The Indonesian Commission for Corruption Eradication - Sudirman Sudirman; Risnita Risnita; Abdul Halim (International Journal of Law and Society, 2026)
Corruption remains a systemic challenge in Indonesia, particularly in the administration of government grant funding, undermining public trust, institutional integrity, and sustainable development. Despite the establishment of the Corruption Eradication Commission (Komisi Pemberantasan Korupsi, KPK) and other specialized bodies, law enforcement continues to face institutional, political, and cultural barriers. This study explores how Islamic criminal law can strengthen anti-corruption strategies by integrating empirical legal practices with normative religious principles. Using a normative-empirical socio-legal approach, the research combines case studies of KPK’s enforcement processes with doctrinal analysis of fiqh jināyah. Data were collected through legal document analysis, policy reviews, and qualitative evaluations of institutional reports and court rulings. Findings indicate that Islamic legal concepts such as khiyānah (breach of trust), ghulūl (misappropriation of public assets), amānah (trustworthiness), ʿadl (justice), and maṣlaḥah (public interest) provide a strong ethical foundation that complements positive law enforcement. While KPK has demonstrated effectiveness in investigation, prosecution, and prevention, its performance is constrained by political pressure, regulatory gaps, and limited resources. The study concludes that embedding Islamic ethical principles into governance, legal education, and public administration can enhance institutional accountability, reinforce preventive measures, and cultivate a culture of integrity. This normative convergence advances socio-legal pluralism and offers practical insights for value-based anti-corruption policy in Indonesia.